2014
DOI: 10.1120/jacmp.v15i4.4514
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of biological versus physical optimization for single‐arc VMAT for prostate and head and neck cases

Abstract: The aim of this work was to compare different approaches to VMAT optimization (biological vs. physical DVH‐based) in two commercial treatment planning systems (TPS) for head and neck and prostate cases, using Pareto fronts. VMAT vs. IMRT Pareto front comparison was additionally performed in order to benchmark the optimizer efficiency and VMAT plan quality for each TPS. Three prostate and three head and neck cancer patients were selected for nine‐beam IMRT and single‐arc VMAT planning in Monaco 3.00 and Oncentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
0
4
0
3
Order By: Relevance
“…Over the last decade, volumetric modulated arc therapy (VMAT) has been explored and implemented to treat a variety of cancers including in the prostate, head and neck, lung, and spine 1, 2, 3, 4. VMAT is a dynamic treatment technique in which the radiation dose rates, gantry speeds, and movements of the multi‐leaf collimator and jaws are simultaneously varied while the beam is on 5.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, volumetric modulated arc therapy (VMAT) has been explored and implemented to treat a variety of cancers including in the prostate, head and neck, lung, and spine 1, 2, 3, 4. VMAT is a dynamic treatment technique in which the radiation dose rates, gantry speeds, and movements of the multi‐leaf collimator and jaws are simultaneously varied while the beam is on 5.…”
Section: Introductionmentioning
confidence: 99%
“…Both IMRT and VMAT are of benefit to the treatment of prostate cancer, as well as head and neck (H&N) cancer, since organs at risk (OARs) in both cases are located close to the target volume, which is irradiated by a typically high prescription dose (4,5,11–13) . Many studies have demonstrated the clinical superiority of both IMRT and VMAT as compared to conventional non‐modulated modalities for the treatment of both prostate and H&N cancer (2,5,11–13) . Furthermore, technological advances in dose calculation algorithm development have enabled more accurate evaluation of treatment plans (14–17) .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, technological advances in dose calculation algorithm development have enabled more accurate evaluation of treatment plans (14–17) . Through utilization of state‐of‐the‐art techniques in radiation therapy, in terms of both calculation and delivery, highly conformal treatment of both prostate and H&N cancer has become possible (2,4,5,12) . However, elaborate treatments with steep dose gradients generated using IMRT and VMAT techniques are more susceptible to errors than are conventional radiation therapy treatments (18,19) .…”
Section: Introductionmentioning
confidence: 99%
“… Μαθηματική ανάλυση και οπτικοποίηση των αποτελεσμάτων (Σχήμα 30). [65] Σχήμα 29. Εισαγωγή εικόνων στο IMRT σύγκριση και ανάλυση.…”
Section: δοσιμετρικος ελεγχος-βελτιστοποιησειςunclassified
“…Υπάρχουν αντίστοιχες μελέτες στη βιβλιογραφία όπου για τον καρκίνο κεφαλής τραχήλου (ρινοφάρυγγα) συγκρίνονται και αξιολογούνται οι τεχνικές IMRT και VMAT [58][59][60][61][62] . Λιγότερες είναι οι μελέτες στις οποίες συγκρίνονται οι αλγόριθμοι βελτιστοποίησης, οι οποίοι στηρίζονται σε βιολογικές ή φυσικές παραμέτρους για τη συγκεκριμένη μορφή καρκίνου [62][63][64][65].…”
Section: υπολογισμός πλάνων ακτινοθεραπείας-κατανομή δόσηςunclassified